ON THE MODE OF UPLIFT OF THE FISH AND FOSSILIFEROUS MORAINES OF THE MCMURDO ICE SHELF, ANTARCTICA. - Gow,A. J.; Weeks,W. F.; Hendrickson,G.; Rowland,R. (1965)
The McMurdo Ice Shelf and associated faunal remains were examined in the vicinity of the easternmost Dailey Island. Stratigraphic, petrographic, and chemical composition studies of cores from 2 holes drilled through the ice shelf show that at these locations the shelf is composed only of fresh water ice. Although cores from the deeper hole possessed glacial textures throughout, much of the ice from this part of the McMurdo Ice Shelf may have been formed from the freezing of a layer of fresh water found sandwiched between the shelf bottom and the underlying sea water. The existence of fresh water under the ice shelf can most probably be attributed to drainage of surface melt water during the ablation season. There was no evidence to indicate that this part of the ice shelf is being nourished by the growth of sea ice onto its lower surface. The fish remains found on the ice surfaces were confined to a narrow zone along the tide crack and are believed to have been left in this vicinity by deep diving seals. The marine invertebrate remains on top of the ice are associated with morainal material and are believed to have been incorporated into the ice at the time of formation of the moraines. (Author)